2023
DOI: 10.21037/gs-22-741
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating a multivariable machine learning model for the preoperative prediction of lateral lymph node metastasis of papillary thyroid cancer

Abstract: Background At present, preoperative diagnosis of lateral cervical lymph node metastasis (LLNM) in patients with papillary thyroid carcinoma (PTC) mostly depends on the training and expertise of ultrasound doctors. A machine-learning model for predicting LLNM accurately before PTC surgery may help to determine the scope of surgery and reduce unnecessary surgical trauma. Methods The data of patients with primary PTC who underwent thyroidectomy with lateral cervical lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The preoperative ultrasound suspicious findings (size of lymph node more than 5 mm, microcalcification, cystic degeneration, round shape, abnormal boundary, and cortical thickening) in addition to clinical data constitute another model[ 73 ]. Some statistical data of ultrasound signs are shown in Table 4 [ 74 ].…”
Section: Pre/postoperative Prediction Factors-recurrencementioning
confidence: 99%
“…The preoperative ultrasound suspicious findings (size of lymph node more than 5 mm, microcalcification, cystic degeneration, round shape, abnormal boundary, and cortical thickening) in addition to clinical data constitute another model[ 73 ]. Some statistical data of ultrasound signs are shown in Table 4 [ 74 ].…”
Section: Pre/postoperative Prediction Factors-recurrencementioning
confidence: 99%
“…The models were trained using the training set, with optimization achieved through a grid search method incorporating ve-fold cross-validation to minimize prediction errors. Model performance in both the training and validation sets was assessed using standard clinical metrics such as the area under the curve (AUC), sensitivity, speci city, precision, recall, accuracy, and F1-score (19). The performance of models in the validation set was identi ed, and the diagnostic performance of the models was compared to select the best classi er.…”
Section: Techniquesmentioning
confidence: 99%
“…Thyroid cancer has become the fastest-growing endocrine malignancy in recent years [1], Among them, papillary thyroid carcinoma (PTC) is the most common histological type, with a 10-year survival rate exceeding 95% [2]. However, the cervical lymph node metastasis (LNM) rate of PTC is as high as 30-80%, especially in the central area [3]. It was reported that patients with central lymph node metastasis (CLNM) might be more likely to have distant metastasis and poor survival than those without CLNM [4].…”
Section: Introductionmentioning
confidence: 99%